Comparison of the Diagnostic Performance of C26:0-Lysophosphatidylcholine and Very Long-Chain Fatty Acids Analysis for Peroxisomal Disorders - Jaspers, Yorrick R. J.; Ferdinandusse, Sacha; Dijkstra, Inge M. E.; Barendsen, Rinse Willem; van Lenthe, Henk; Kulik, Wim; Engelen, Marc; Goorden, Susan M. I.; Vaz, Frédéric M.; Kemp, Stephan (Frontiers in Cell and Developmental Biology, 2020)
Peroxisomes are subcellular organelles that are involved in various important physiological processes such as the oxidation of fatty acids and the biosynthesis of bile acids and plasmalogens. The gold standard in the diagnostic work-up for patients with peroxisomal disorders is the analysis of very long-chain fatty acid (VLCFA) levels in plasma. Alternatively, C26:0-lysophosphatidylcholine (C26:0-LPC) can be measured in dried blood spots (DBS) using liquid chromatography tandem mass spectrometry (LC-MS/MS); a fast and easy method but not yet widely used. Currently, little is known about the correlation of C26:0-LPC in DBS and C26:0-LPC in plasma, and how C26:0-LPC analysis compares to VLCFA analysis in diagnostic performance. We investigated the correlation between C26:0-LPC levels measured in DBS and plasma prepared from the same blood sample. For this analysis we included 43 controls and 38 adrenoleukodystrophy (ALD) (21 males and 17 females) and 33 Zellweger spectrum disorder (ZSD) patients. In combined control and patient samples there was a strong positive correlation between DBS and plasma C26:0-LPC (Spearman’s rank correlation coefficient of r (114) = 0.962, p < 0.001). These data show that both plasma and DBS are suitable to determine blood C26:0-LPC levels and that there is a strong correlation between C26:0-LPC levels in both matrices. Following this, we investigated how VLCFA and C26:0-LPC analysis compare in diagnostic performance for 67 controls, 26 ALD males, 19 ALD females, and 35 ZSD patients. For C26:0-LPC, all ALD and ZSD samples had C26:0-LPC levels above the upper limit of the reference range. For C26:0, one out of 67 controls had C26:0 levels above the upper reference range. For 1 out of 26 (1/26) ALD males, 1/19 ALD females and 3/35 ZSD patients, the C26:0 concentration was within the reference range. The C26:0/C22:0 ratio was within the reference range for 0/26 ALD males, 1/19 ALD females and 2/35 ZSD patients. Overall, these data demonstrate that C26:0-LPC analysis has a superior diagnostic performance compared to VLCFA analysis (C26:0 and C26:0/C22:0 ratio) in all patient groups. Based on our results we recommend implementation of C26:0-LPC analysis in DBS and/or plasma in the diagnostic work-up for peroxisomal disorders.